2023
DOI: 10.3389/fendo.2023.1289574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blood flow restriction exercise on N-lactoylphenylalanine and appetite regulation in obese adults: a cross-design study

Shuoqi Li,
Rong Guo,
Juncheng Wang
et al.

Abstract: BackgroundN-lactoylphenylalanine (Lac-Phe) is a new form of “exerkines” closely related to lactate (La), which may be able to inhibit appetite. Blood flow restriction (BFR) can lead to local tissue hypoxia and increase lactate accumulation. Therefore, this study investigated the effects of combining Moderate-intensity Continuous Exercise (MICE) with BFR on Lac-Phe and appetite regulation in obese adults.MethodsThis study employed the cross-design study and recruited 14 obese adults aged 18-24 years. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Exercise intervention can reduce oxidative stress, increase mitochondrial capacity, and enhance mitochondrial function [ 3 ]. Furthermore, it is particularly noteworthy that research has identified the combination of moderate-intensity continuous exercise (MICE) with blood flow restriction (BFR) as effective in suppressing the appetite of obese adults through the promotion of Lac-Phe and ghrelin secretion [ 4 ]. This finding underscores the significant implications of exercise not only for CKD but also for diabetes management, highlighting its potential as a pivotal intervention in the treatment and prevention strategies for these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise intervention can reduce oxidative stress, increase mitochondrial capacity, and enhance mitochondrial function [ 3 ]. Furthermore, it is particularly noteworthy that research has identified the combination of moderate-intensity continuous exercise (MICE) with blood flow restriction (BFR) as effective in suppressing the appetite of obese adults through the promotion of Lac-Phe and ghrelin secretion [ 4 ]. This finding underscores the significant implications of exercise not only for CKD but also for diabetes management, highlighting its potential as a pivotal intervention in the treatment and prevention strategies for these conditions.…”
Section: Introductionmentioning
confidence: 99%